Concordant and Heterogeneity of Single-Cell Transcriptome in Cardiac Development of Human and Mouse - Shang, Mengyue; Hu, Yi; Cao, Huaming; Lin, Qin; Yi, Na; Zhang, Junfang; Gu, Yanqiong; Yang, Yujie; He, Siyu; Lu, Min; Peng, Luying; Li, Li (Frontiers in Genetics, 2022)
The normal heart development is vital for maintaining its function. The development process is involved in complex interactions between different cell lineages. How mammalian hearts develop differently is still not fully understood. In this study, we identified several major types of cardiac cells, including cardiomyocytes (CMs), fibroblasts (FBs), endothelial cells (ECs), ECs/FBs, epicardial cells (EPs) and immune cells (macrophage/monocyte cluster, MACs/MONOs), based on single-cell transcriptome data from embryonic hearts of both human and mouse. Then, species-shared and species-specific marker genes were determined in same cell type between the two species, and the genes with consistent and different expression patterns were also selected by constructing the developmental trajectories. Through comparison of the development stage similarity of CMs, FBs and ECs/FBs between human and mouse, it is revealed that CMs at e9.5 and e10.5 of mouse are most similar to those of human at 7W and 9W, respectively. Mouse FBs at e10.5, e13.5 and e14.5 are correspondingly more like to the same human cells at 6W, 7W and 9W. Moreover, the e9.5-ECs/FBs of mouse are most similar to that of human at 10W. These results provide a resource for understudying cardiac cell types and the crucial markers able to trace developmental trajectories among the species, which is benefit for finding suitable mouse model to detect human cardiac physiology and related diseases.